Keith B. Griffin y John L. Enos. Planning development. Londres : Addison-Wesley Publishing Company, 1970. 293 p. - Rodríguez y González, Alejandro (El Colegio de México A.C., 1973)
KEITH B. GRIFFIN y JOHN L. ENOS, Planning Development, Londres, Addison-Wesley Publishing Company, 1970.